Reconsidering the role of orthographic redundancy in visual word recognition - Chetail, Fabienne (Frontiers in Psychology, 2015)
Humans are known to continuously extract regularities from the flow of stimulation. This occurs in many facets of behaviour, including reading. In spite of the ubiquitous evidence that readers become sensitive to orthographic regularities after very little exposure to print, the role of orthographic regularities receives at best a peripheral status in current theories of orthographic processing. In the present article, after the presentation of previous evidence on orthographic redundancy, the hypothesis that orthographic regularities may play a prominent role in word perception is developed.